Quorum Sensing Controls the CRISPR and Type VI Secretion Systems in Aliivibrio wodanis 06/09/139 - Maharajan, Amudha Deepalakshmi; Hjerde, Erik; Hansen, Hilde; Willassen, Nils Peder (Frontiers in Veterinary Science, 2022)
For bacteria to thrive in an environment with competitors, phages and environmental cues, they use different strategies, including Type VI Secretion Systems (T6SSs) and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) to compete for space. Bacteria often use quorum sensing (QS), to coordinate their behavior as the cell density increases. Like other aliivibrios, Aliivibrio wodanis 06/09/139 harbors two QS systems, the main LuxS/LuxPQ system and an N-acyl homoserine lactone (AHL)-mediated AinS/AinR system and a master QS regulator, LitR. To explore the QS and survival strategies, we performed genome analysis and gene expression profiling on A. wodanis and two QS mutants (ΔainS and ΔlitR) at two cell densities (OD600 2.0 and 6.0) and temperatures (6°C and 12°C). Genome analysis of A. wodanis revealed two CRISPR systems, one without a cas loci (CRISPR system 1) and a type I-F CRISPR system (CRISPR system 2). Our analysis also identified three main T6SS clusters (T6SS1, T6SS2 and T6SS3) and four auxiliary clusters, as well about 80 potential Type VI secretion effectors (T6SEs). When comparing the wildtype transcriptome data at different cell densities and temperatures, 13 to 18% of the genes were differentially expressed. The CRISPR system 2 was cell density and temperature-independent, whereas the CRISPR system 1 was temperature-dependent and cell density-independent. The primary and auxiliary clusters of T6SSs were both cell density and temperature-dependent. In the ΔlitR and ΔainS mutants, several CRISPR and T6SS related genes were differentially expressed. Deletion of litR resulted in decreased expression of CRISPR system 1 and increased expression of CRISPR system 2. The T6SS1 and T6SS2 gene clusters were less expressed while the T6SS3 cluster was highly expressed in ΔlitR. Moreover, in ΔlitR, the hcp1 gene was strongly activated at 6°C compared to 12°C. AinS positively affected the csy genes in the CRISPR system 2 but did not affect the CRISPR arrays. Although AinS did not significantly affect the expression of T6SSs, the hallmark genes of T6SS (hcp and vgrG) were AinS-dependent. The work demonstrates that T6SSs and CRISPR systems in A. wodanis are QS dependent and may play an essential role in survival in its natural environment.